Géohistoire des frontières sahariennes. L’héritage nomade enseveli sous les murs de sable - Laurent Gagnol (Bulletin de l’Association de Géographes Français, 2022)
Based on the exemplary case of the borders in the central Sahara that separate the Sahel states from the Maghreb states, this analysis shows the reinforcement of a security conception of the border that is now being generalized to these peripheral regions, which are often considered as ‘grey zones’ with porous borders. By shedding light on a phenomenon that has been little or not at all documented and is now revealed by satellite imagery – the construction of sand walls at the borders – we will show that the largest desert in the world is not or is no longer the smooth and boundless space of the Western imagination. More broadly, based on a long-term geohistorical approach, the interweaving and evolution of three successive border regimes are highlighted: a pre-colonial regime under the domination of Tuareg caravan nomadism and structured on the basis of border wells; a colonial and post-colonial regime imposing a Westphalian conception of the border; and the contemporary security regime which participates in the partitioning of the Sahara by sand walls.